Digital ischaemia aetiologies and mid-term follow-up: A cohort study of 323 patients. Issue 20 (21st May 2021) - Raimbeau, Alizée; Pistorius, Marc-Antoine; Goueffic, Yann; Connault, Jérôme; Plissonneau-Duquene, Pierre; Maurel, Blandine; Reignier, Jean; Asehnoune, Karim; Artifoni, Mathieu; Didier, Quentin; Gautier, Giovanni; Trochu, Jean-Nöel; et al.
Abstract : Abstract: Upper extremity digital ischaemia (UEDI) is a rare heterogeneous condition whose frequency is 40 times less than that of toe ischaemia. Using a large cohort, the aim of this study was to evaluate aetiologies, prognosis and midterm clinical outcomes of UEDI. All patients with UEDI with or without cutaneous necrosis in a university hospital setting between January 2000 to December 2016 were included. Aetiologies, recurrence of UEDI, digital amputation and survival were analyzed retrospectively. Three hundred twenty three patients were included. UEDI due to cardio-embolic disease (DICE) was the highest occurring aetiology with 59 patients (18.3%), followed by DI due to Systemic Sclerosis (SSc) (16.1%), idiopathic causes (11.7%), Thromboangiitis obliterans (TAO) (9.3%), iatrogenic causes (9.3%), and cancer (6.2%). DICE patients tended to be older and featured more cases with arterial hypertension whereas TAO patients smoked more tobacco and cannabis. During follow-up, recurrences were significantly more frequent in SSc than in all other tested groups ( P  < .0001 vs idiopathic and DICE, P  = .003 vs TAO) and among TAO patients when compared to DICE patients ( P  = .005). The cumulated rate of digital amputation was higher in the SSc group (n = 18) ( P  = .02) and the TAO group (n = 7) ( P  = .03) than in DICE (n = 2). This retrospective study suggests that main aetiologies of UEDI are DICE, SSc and idiopathic. This study highlights higher frequency of iatrogenic UEDI than previous studies. UEDI associated with SSc has a poor local prognosis (amputations and recurrences) and DICE a poor survival. UEDI with SSc and TAO are frequently recurrent.